2016
DOI: 10.1111/1541-4337.12245
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Food Safety Hazards in the European Dairy Supply Chain

Abstract: Monitoring of dairy products should preferably focus on the most relevant food safety hazards in the dairy supply chain. For this purpose, the possible presence of microbiological, chemical, and physical hazards as well as trends in the dairy supply chain that may affect their presence were assessed. A literature review was combined with available data from EFSA, RASFF, and the Dutch monitoring program on chemical hazards as well as expert information. This study revealed that microbiological hazards are encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 101 publications
1
136
0
5
Order By: Relevance
“…Milk contamination is hence a result of direct exposure to fecal material or environmental contamination. Raw milk poses a risk for STEC, and a number of outbreaks has been recently reported for this pathogen [33,36]. In 2013, 3% of 860 tested raw milk samples were found positive for STEC in Europe [33], whereas in USA, according to CDC, Shiga toxin-producing E. coli caused 17% of the outbreaks that occurred 2007 to 2012.…”
Section: Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Milk contamination is hence a result of direct exposure to fecal material or environmental contamination. Raw milk poses a risk for STEC, and a number of outbreaks has been recently reported for this pathogen [33,36]. In 2013, 3% of 860 tested raw milk samples were found positive for STEC in Europe [33], whereas in USA, according to CDC, Shiga toxin-producing E. coli caused 17% of the outbreaks that occurred 2007 to 2012.…”
Section: Fungimentioning
confidence: 99%
“…Raw milk poses a risk for STEC, and a number of outbreaks has been recently reported for this pathogen [33,36]. In 2013, 3% of 860 tested raw milk samples were found positive for STEC in Europe [33], whereas in USA, according to CDC, Shiga toxin-producing E. coli caused 17% of the outbreaks that occurred 2007 to 2012. VTEC serotypes have also been detected in cow's mastitic milk, that implying that an additional contamination route may be sub-clinical mammary infections.…”
Section: Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Food safety hazards in the dairy supply chain may be biological, chemical, or physical in nature (Smith, 2016;van Asselt et al, 2017). A comprehensive review of hazards in the dairy supply chain in Europe found that microbiological hazards are of particular concern, with chemical and physical hazards less frequently encountered in dairy products (van Asselt et al, 2017).…”
Section: Foodborne Hazardsmentioning
confidence: 99%
“…On the other hand, during postharvest processing, storage, and transportation, physiological qualities of harvested foods continue changing. Food safety hazards must be effectively monitored by the food industry (Asselt and others ). Any pathogenic infestation, adulteration, contamination, or defect of plant foods, existing deliberately or accidentally, can not only reduce their functional properties and nutritive values, but also may cause a series of foodborne illnesses in humans.…”
Section: Introductionmentioning
confidence: 99%